Exploring the Gender Gap: Motivation, Procrastination, Environment, and Academic Performance in an Introductory Physics Course in a Human-Centered Private University in Northeast Mexico-A Case Study - Humberto Martínez-Huerta; Wendy Xiomara Chavarría-Garza; Osvaldo Aquines-Gutiérrez; Ayax Santos-Guevara (MDPI AG, 2024)
Progress has been made in recent decades toward achieving gender equality, but today, the gender gap is still noticeable, especially in STEM fields. In support of Goal 5 of the 2030 Sustainable Development Agenda: achieve gender equality and empower all women and girls, we analyze the context of a private university in northeastern Mexico using a sample of 249 students (157 males and 92 females) enrolled in the first-year engineering course Physics I. The sample presents better academic performance in favor of women by the end of the course as reported through the final course score (F); thus, we explore potential gender differences in student profiles, such as their motivation and level of procrastination using Kruskal-Wallis correlation tests, and measuring the effect size with Cohen's d. Our tests reported here reveal significant differences in extrinsic motivation (EMO) and intrinsic motivation (IMO), where females obtained higher means in IMO, while males reported higher levels of procrastination (PRO). Contrary to other cases in the literature, the sample presents better academic performance in favor of women. Our findings here aim to encourage programs and strategies that strengthen women's intrinsic motivation to support women's empowerment and keep reducing the gender gap.